MENINGKATKAN HASIL BELAJAR IPA DENGAN PENERAPAN METODE PEMBELAJARAN KOOPERATIF TIPE NUMBERED HEADS TOGETHER (NHT) DI KELAS V SDN 010 LANGGINI KECAMATAN BANGKINANG KOTA - Abu Bakar (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2018)
The low learning outcomes of science are the background of this study, for this reason, improvements in learning are carried outby applying the NHT method. The purpose of this study is to improve science learning outcomes. This research is a classroomaction research, which was conducted in SD Negeri 010 Langgini. The subjects of this study were class V students with a total of18 students. The results showed that there was an increase in student learning outcomes in cycle 1 meeting 1 the number ofstudents completed was 8, at meeting 2 increased by 12, in cycle 2 meeting 1 increased to 15 and at meeting 2 the number ofstudents who completed increased by 18 Then it can be concluded that through the use of NHT learning methods can improve thelearning outcomes of fifth grade students of SD Negeri 010 Langgini.